EVALUATION OF THE APPLICATION OF SOCIAL INTERACTION THEORY IN INSTILLING CHARACTER VALUES: IMPLEMENTATION IN PAI SUBJECTS IN ISLAMIC EDUCATIONAL INSTITUTIONS - Wahyuni, Sri; Ernawati, Ernawati; Muhajir, Muhajir; Hatip, Ahmad (Jurnal Konseling Pendidikan Islam, 2024)
This research aims to evaluate the application of social interaction theory in instilling character values within Islamic Religious Education (PAI) subjects at Islamic educational institutions. The study investigates the extent to which social interaction theory is applied, the factors influencing its effectiveness, and the impact of social interaction on students' character formation. A qualitative approach was utilized, employing a case study design. Data were collected through in-depth interviews with PAI teachers, school administrators, and students, as well as classroom observations and document analysis. Thematic analysis was used to identify patterns and themes from the data. The findings reveal that social interaction plays a significant role in character education, especially when teachers actively engage students in discussions, peer collaboration, and group work. Schools that provide adequate institutional support and have smaller class sizes create an environment where social interaction can flourish, leading to stronger internalization of values such as empathy, respect, and responsibility. However, the study also highlights challenges such as rigid curricula, cultural resistance, and technological limitations, which hinder the effective implementation of interactive learning methods. In conclusion, social interaction theory offers a valuable framework for character development in PAI learning. Its success depends on the commitment of educators and institutions to fostering collaborative and reflective learning environments. Addressing the identified challenges will be essential for maximizing the benefits of social interaction in character education.